Trade integration: its threats and opportunities for agricultural exports between EU, CIS and Russia - Erokhin, Vasilii (Henry Stewart Talks, 2014)
World trade in agricultural products, World markets of selected agricultural products (wheat, sugar, corn), International market of green products, EU-27 trade in agricultural products, Russian domestic market of agricultural products and external trade in agricultural commodities, WTO membership of separate CIS countries